Analysis of the Transition Strategy to a Digital System at PT BPRS Al Washliyah Medan: Opportunities and Challenges - Haviz, Luthfi; Maidalena, Maidalena; Nasution, Muhammad Lathief Ilhamy (Journal of Economics and Management Scienties, 2025)
Digital transformation, which is the integration of digital technology into all aspects of business operations, fundamentally changes the way organizations operate and deliver value to customers. This research aims to analyze the transition strategy to a digital system at PT BPRS Al-Washliyah Medan, with a focus on identifying opportunities, challenges, and optimal strategies that can be applied in the digital transformation process. The method used is descriptive qualitative with a case study approach, through interviews, observations, and document studies. The research results show that although BPRS Al-Washliyah faces internal limitations such as technological infrastructure and human resources, this institution has great potential to develop through a gradual digital approach, adaptive strategies, and regulatory support. Digital transformation is deemed important to strengthen competitiveness, communication effectiveness, and the institution's image amidst the dynamics of the Islamic banking industry.